Agreement between Western Michigan University and the WMU Chapter of the American Association of University Professors for September 5, 1984-September 6, 1987 - American Association of Univ. Professors, Washington, DC.; American Association of Univ. Professors, Washington, DC.; Western Michigan Univ., Kalamazoo ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
The collective bargaining agreement between Western Michigan University and the Western Michigan University Chapter (805 members) of the American Association of University Professors (AAUP) covering the period September 5, 1984--September 6, 1987 is presented. Items covered in the agreement include: definitions and AAUP recognition, management and union rights, past practices, union right to data, union access to facilities and services, board of trustees observer, agency shop, antidiscrimination and affirmative action, personnel files, grievance procedure, academic freedom and responsibility, faculty appointment and reappointment, nepotism, promotion policy and procedure, tenure policy, evaluation of faculty, faculty evaluation of academic administrators, faculty termination, dismissal and discipline for cause, faculty participation in departmental governance, layoff and recall, sabbatical leave policy, leaves of absence, additional employment, community service, compensation guidelines, economic compensation, faculty research and creative activities fund, faculty research travel fund, retirement, fringe benefits, long range planning, university calendar, annual survey of faculty, faculty development policy, work of the unit and preference, patents and copyrights, no strike/lockout, waiver clause, savings provision, employee assistance program, and permanent interdepartmental transfer process. Appendices cover: rules of conduct, faculty senate, memorandum of understanding, tenure decisions, and arbitration panel. Letters of understanding are provided on alternate academic year appointments, compensation, evaluation of faculty, faculty participation in departmental governance, and tuition waiver. (SW)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Arbitration; Collective Bargaining; College Faculty; Contracts; Employment Practices; Faculty Evaluation; Faculty Promotion; Faculty Workload; Governance; Grievance Procedures; Higher Education; Leaves of Absence; Participative Decision Making; Personnel Policy; State Universities; Teacher Dismissal; Teacher Employment Benefits; Teacher Salaries; Tenure; Unions; AAUP Contracts -- Western Michigan University; American Association of University Professors -- Faculty Reappointment -- Personnel Files -- Tuition Benefit Programs -- Union Rights; Legal/Legislative/Regulatory Materials